The newly-found petroglyphs of Ariyeh in Khorasan Razavi province, North-Eastern Iran. (December 2022) - Basafa, Hassan; Masihniya, Farshid; Sigari, Dario
Abstract: Despite the distribution of known rock art in Iran showing a main concentration in central and western Iran, research activities undertaken in the very last decades led to the identification of sites in eastern Iran as well. In 2018 a new rock art site was discovered close to Ariyeh, Khorasan Razavi province, NE Iran. Here we present a case report on these newly found petroglyphs that are now in imminent danger due to recent vandalism. According to the represented iconography, its features, style, and patina, it seems that the Ariyeh rock art was produced over a long chronology, from the late Prehistory to the Islamic period. The discovery of the petroglyphs of Ariyeh has strong implications towards the understanding of the relationships among the different sites and their use, function, and meaning, in order to understand cultural connections occurred between the Iranian plateau and the surrounding areas over the millennia.